Association of serum leptin and adiponectin with anthropomorphic indices of obesity, blood lipids and insulin resistance in a Sub-Saharan African population - Ayina, Clarisse Noël A. (Lipids Health Dis, 2016)
BACKGROUND: There is little data on the metabolic effects of adipokines in sub-Saharan African populations. This study aimed to explore the potential relationship of leptin and adiponectin, with obesity, plasma lipids and insulin resistance in a Cameroonian population. METHODS: We enrolled 167 men and 309 women aged ≥18 years from the general population in Cameroon. Data were collected on waist circumference (WC), body mass index (BMI), waist-to-hip ratio (WHR), body fat (BF%), fasting blood glucose, plasma lipids, adiponectin, leptin, insulin and homeostasis model for assessment of insulin resistance (HOMA-IR). Pearson’s correlation and multiple stepwise linear regression analyses were used to determine correlates of leptin and adiponectin serum levels. RESULTS: The prevalence of obesity was higher in women compared to men (p < 0.0001), and Central obesity which is more prevalent particularly in women (WC = 42.4 %, WHR = 42.3 %), is almost for 90 % comparable to %BF (42.7 %). Adiponectin negatively with BMI (r = −0.294, p < 0.0001), WC (r = −0.294, p < 0.0001), %BF (r = −0.122, p = 0.028), WHR (r = −0.143, p = 0.009), triglycerides (r = −0.141, p = 0.011), HOMA-IR (r = −0.145, p = 0.027) and insulin (r = −0.130, p = 0.048). Leptin positively correlated with BMI (r = 0.628), WC (r = 0.530), BF% (r = 0.720), (all p < 0.0001); with DBP (r = 0.112, p = 0.043), total cholesterol (r = 0.324, p < 0.0001), LDL-cholesterol (r = 0.298, p < 0.0001), insulin (r = 0.320, p < 0.001 and HOMA-IR (r = 0.272, p < 0.0001). In multiple stepwise regression analysis, adiponectin was negatively associated with WC (β = −0.38, p = 0.001) and BF% (β = 0.33, p < 0.0001), while leptin was positively associated with BF% (β = 0.60, p < 0.0001), total cholesterol (β = 0.11, p = 0.02) and HOMA-IR (β = 0.11, p = 0.02). When controlled for gender, HOMA-IR was found significantly associated to adiponectin (β = 0.13, p = 0.046), but not BF%, while the association previously found between leptin and HOMA-IR disappeared; BMI and WC were significantly associated with leptin (β = 0.18, p = 0.04 & β = 0.19, p = 0.02 respectively). CONCLUSION: This study, which includes a population who was not receiving potentially confounding medications, confirms the associations previously observed of adiponectin with reduced adiposity especially central adiposity and improved insulin sensitivity. Confirmatory associations were also observed between leptin and obesity, blood lipids and insulin resistance for the first time in an African population. Gender was significant covariate interacting with insulin sensitivity/insulin resistance and obesity indexes associations in this population.